2018
DOI: 10.31083/j.rcm.2018.04.3187
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Effects of Chocolate

Abstract: The antioxidants as polyphenols, especially flavanols present in cocoa, exert a favorable effect on endothelium vasodilation, modulate inflammatory markers, and decrease platelet aggregation, lipid oxidation and insulin resistance. Recent nutritional intervention trials and molecular studies demonstrate that consumption of cocoa, particularly rich in flavanols, is beneficial to promote cardiovascular health. This review describes the cardiovascular effects of chocolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…Citrus flavanones were also found to modulate the JNK/p38 MAPK pathway, which has been previously reported to play a significant role in the development of DCM [ 4 , 17 ], especially via the promotion of cardiomyocytes inflammation and apoptosis. Musolino et al [ 17 ] reported that via this pathway, bergamot polyphenols, which are rich in flavanone naringin and hesperidin, were able to ameliorate insulin sensitivity along with their potent antioxidative properties, further supporting their therapeutic use for the management of DCM [ 119 , 120 ]. Hesperidin and its aglycone derivative hesperetin are both found abundantly in citrus fruits and showed to be able to protect the heart against doxorubicin-induced oxidative stress by improving cardiac antioxidants levels [ 121 ].…”
Section: Therapeutic Role Of Flavonoid In Inhibiting Dcm Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Citrus flavanones were also found to modulate the JNK/p38 MAPK pathway, which has been previously reported to play a significant role in the development of DCM [ 4 , 17 ], especially via the promotion of cardiomyocytes inflammation and apoptosis. Musolino et al [ 17 ] reported that via this pathway, bergamot polyphenols, which are rich in flavanone naringin and hesperidin, were able to ameliorate insulin sensitivity along with their potent antioxidative properties, further supporting their therapeutic use for the management of DCM [ 119 , 120 ]. Hesperidin and its aglycone derivative hesperetin are both found abundantly in citrus fruits and showed to be able to protect the heart against doxorubicin-induced oxidative stress by improving cardiac antioxidants levels [ 121 ].…”
Section: Therapeutic Role Of Flavonoid In Inhibiting Dcm Developmentmentioning
confidence: 95%
“…They have been reported to exhibit diverse therapeutic potential in medicine and other biological activities [ 12 , 13 , 14 ]. The potential of flavonoids in alleviating diabetic cardiomyopathy or other cardiovascular complications derived from diabetes have been commonly related with their remedial actions as anti-hyperglycemic [ 15 ], anti-hyperlipidemic [ 16 ], antioxidant [ 17 ], anti-inflammatory [ 18 ], and anti-apoptotic [ 19 ] agents. Considering the promising potential of flavonoids in combating diabetic cardiomyopathy development, we aimed to review the potential mechanisms that flavonoids and their subclasses target in order to exert their cardioprotective potential.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, polyphenol-rich products as black tea, green tea, and red grape extracts improve FMD in individuals with coronary artery disease (Andriantsitohaina et al, 2012). Nutritional supplements rich in polyphenols such as chocolate (Garcia et al, 2018) and walnut extract (Papoutsi et al, 2008) could also have potential effects on blood vessels.…”
Section: Polyphenols and Other Natural Extractsmentioning
confidence: 99%
“…Among them, flavonoids, such as puerarin, daidzin, luteolin, calycosin-7-O-β-D-glucoside, calycosin and formononetin, are the most abundant. They can alleviate diabetic cardiomyopathy or other cardiovascular complications by their anti-hyperglycemia, 18 anti-hyperlipidemia, 19 anti-oxidant, 20 anti-inflammatory 21 and anti-apoptotic 22 functions. Small peptides, such as N-Acetyl-D-leucine, Cyclo (leucylprolyl) and N-Acetyl-L-phenylalanine are considered to be a new generation of modulators of biological activity, which can prevent cellular oxidation and inflammation, and can be used to prevent the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%